RANCANG BANGUN SISTEM INFORMASI PEMASARAN TOKO “OEMAH BAJOE DY ANNISA” (Information Technology and Telematics, 2014)
Abstract - In entering the world of globalization, people familiar with the more advanced technology to facilitate the conduct of various activities in life. Progress in the field of transportation, communication, health, education, and other fields is an example of technology that people increasingly need in this life. Today the world has known a technology called the Internet. With all the internet people can communicate with others who are in different parts of the world. Through the Internet, everyone can obtain and deliver required information anytime and anywhere. Now, with the presence of the internet, people can do business more easily.This study will create a marketing information system or often called a web-based e-commerce using Java programming, MySQL and PHP to be used to assist the user in an area to make the process of buying or ordering goods without having all the way dating to the store "Oemah Bajoe Dy Annisa ".Keywords: marketing information systems, E-commerce.